No god but god : the origins, evolution, and future of islam - Aslan, Reza. ([S.l.] : Arrow, 2011)
*Ten years on from 9/11, much of the Muslim faith remains largely unknown and misunderstood in the West. *While there have been a number of successful books on the topic of Islamic history - from Karen Armstrong's Islam: A Brief History to Bernard Lewis's The Crises of Islam - there is surprisingly no book for a popular audience about Islam as a religion, let alone one by an author from an Islamic background. *No God But God fills that gap, addressing issues of belief: the difference between the Quran and the Bible, the meaning of the Hajj, the Muslim relationship with Jesus, the Muslim attitude towards Jews, equality between the sexes and more. * This revised and updated edition includes a wealth of new material and new chapters covering recent uprisings in Tunisia, Egypt and Libya; the changing face of Islam in Europe and North Africa; and a number of topics of heated debate (the veil controversy; Islam & women; Iraq War as a Jihadi recruiting agent etc).
International Edition.
Keywords: Islam; Islam--Essence, genius, nature